A history of the quests for the historical Jesus: from the post-war era through contemporary debates - Brown, Colin, 1932-; Evans, Craig A. (Grand Rapids: Zondervan academic, 2022)
"A History of the Quests for the Historical Jesus is an extensive survey and analysis of historical Jesus debates, assessing not only the quests' historical, exegetical, critical details but also their philosophical and theological underpinnings"--
volume 1. From the beginnings of Christianity to the end of World War II -- volume 2. From the post-war era through contemporary debates.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Biography -- History and criticism; Jesus Christ -- Historicity; Jesus Christ -- History of doctrines